Business plan - Hakim, Pariso (2025)
This thesis presents a comprehensive business plan for establishing a Tajik restaurant in Prague. The primary objective is to assess the market potential, financial feasibility, and operational requirements of introducing Tajik cuisine into the local gastronomic environment. The study integrates both theoretical approaches and practical analysis, combining tools such as PESTLE, Porter’s Five Forces, SWOT analysis, customer surveys, and financial forecasting. The research identifies opportunities within Prague’s diverse and expanding culinary market, supported by a favorable location, growing tourism, and rising consumer interest in ethnic dining experiences. At the same time, the study highlights several challenges, including limited awareness of Tajik cuisine, high startup and operating costs, and exposure to economic and regulatory risks. Financial projections indicate that while the restaurant may achieve moderate profitability in the long term, the early years are likely to be financially constrained. The thesis concludes that the project carries significant risk and may not generate high short-term returns. However, with a clearly defined strategy, effective marketing, and strong operational planning, the restaurant has the potential to contribute to Prague’s multicultural dining landscape and promote Tajik culinary heritage. The business plan offers a structured guide for implementation, while also serving as a case study for evaluating the viability of culturally distinctive restaurant ventures in competitive urban markets.